1944
DOI: 10.1063/1.1707453
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Bubbles

Abstract: Extreme values for the negative pressures and the degrees of superheat which water will withstand without forming bubbles are contrasted with the ease of forming bubbles by vibration or by the turbulent flow of liquids. The subject of bubble nuclei is briefly reviewed, and it is pointed out that such nuclei usually function by virtue of sorbed or trapped air which can be removed, rendering the nuclei ineffective. Technique for avoiding extraneous bubble nuclei is presented with some experiments on the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

1944
1944
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…The nucleation and subsequent detachment and flow of bubbles in a system is a process that effects a wide spectrum of industries, often with undesirable results.As originally reported by Dean [1], the formation of bubbles finds its origins in the presence of either a supersaturated or a superheated liquid.A number of recent studies have published data on the subject of bubble formation in supersaturated conditions and turbulent bubbly flow in ducts. However, in spite of the inherent importance of this subject in relation to heating systems, the authors of this study are not aware of published data relating to bubble characteristics observed in wet domestic central heating systems.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The nucleation and subsequent detachment and flow of bubbles in a system is a process that effects a wide spectrum of industries, often with undesirable results.As originally reported by Dean [1], the formation of bubbles finds its origins in the presence of either a supersaturated or a superheated liquid.A number of recent studies have published data on the subject of bubble formation in supersaturated conditions and turbulent bubbly flow in ducts. However, in spite of the inherent importance of this subject in relation to heating systems, the authors of this study are not aware of published data relating to bubble characteristics observed in wet domestic central heating systems.…”
Section: Introductionmentioning
confidence: 87%
“…The authors of this study understand that classical theory for bubble nucleation asdefined by Dean [1] suggests that under saturation conditions should not result in bubble nucleation due to the bulk fluid pressure being higher than the gas pressure in a bubble, thus inhibiting growth of existing gas cavities. The release of micro bubbles from the boiler tubes at under saturation conditions in the present study could be attributed to unmonitored high temperatures on the boiler wall that result in localised supersaturation areas at the boiler wall conditions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…The focal events responsible for the initial production of the bubbles, while of immense theoretical interest, do not relate specifically to the problem at hand. As discussed so adequately by HARVEY and his co-workers (1951); DEAN (1944);PEASE and BLINKS (1957); and more recently by LIEBERMAN (1957) and WEBSTER (1963), bubbles may arise in solution from preformed micronuclei or de novo from cavitation events. It would appear that formation of vacuum cavities by muscle and joint movement or in vortices of turbulent zones of blood flow is a more probable source of bubble nuclei (ROTH, 1965).…”
Section: Decompression Sicknessmentioning
confidence: 99%
“…One of these is that cavitation can be associated with vorticity, as it was first proposed already in 1944 by Dean [26], and developed by McConnell, Chu and Finch [27], who considered a mechanism of ultrasonic cavitation in liquid helium by quantized vortices. It seems clear that the velocity field of a single quantized vortex is much too weak to affect the nucleation barrier appreciably.…”
Section: On the Possible Role Of Impurities Solid Surfaces Radiatiomentioning
confidence: 99%